Kompetensi Menulis Karya Ilmiah Mahasiswa Program Studi Manajemen STIE Manajemen Bisnis Indonesia Depok Jawa Barat - H. Purnomo, H. Purnomo; Putri Lubis, Amanda Lestarie; Nurliyah, Elly Siti; Kartikaningsih, Dewi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine students' ability to write scientific papers and also find out the obstacles experienced by students in scientific writing. Management study program students at STIE MBI (Indonesian Business Management) are the object of this research, and quantitative-descriptive is the research method used in this research. All students enrolled in the STIE MBI management study program for semester 7 (seven) of the 2022–2023 academic year were included in this study population. The sample consisted of 35 students who were randomly selected. Data for the Risk Management and Organizational Culture course are collected in the form of scientific papers, which are then analyzed using research instrument tables. Based on the research findings, it was found that 26% of the students got good marks, followed by 51% who got enough marks (18 students), 14% who got low scores (5 students), and 9% who got very low scores (3 students). So the conclusion is that the competency abilities of STIE MBI (Indonesian Business Management) management study program students in writing scientific papers are on average sufficient or moderate; it is necessary to improve.